2011
DOI: 10.2320/matertrans.m2010407
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Synthesis of CaMoO<SUB>4</SUB> Nanocolloidal Suspension and Its Optical Properties

Abstract: Pulsed laser ablation in a liquid phase was employed successfully to synthesize a calcium molybdate (CaMoO 4 ) nanocolloidal suspension. The crystalline phase, particle morphology, particle size distribution, absorbance, optical band-gap and photoluminescence (PL) were examined. Stable colloidal suspensions consisting of well-dispersed CaMoO 4 nanoparticles with a narrow size distribution could be obtained without a surfactant. The optical absorption edge located near 270 nm was blue-shifted by approximately 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Such transitions are normally related to the electron-hole recombination process after excitation using the band gap of the O-Mo charge transfer transition in MoO 4 tetrahedra. 48 It is reported that in the case of CaMoO 4 emission peak maxima normally appear to be around 480-510 nm 46,47 but they are blue shifted if the size is in a nano-domain 48 due to the quantum confinement effect.…”
Section: Emission Spectroscopy Of Camoo 4 and Srmoomentioning
confidence: 99%
“…Such transitions are normally related to the electron-hole recombination process after excitation using the band gap of the O-Mo charge transfer transition in MoO 4 tetrahedra. 48 It is reported that in the case of CaMoO 4 emission peak maxima normally appear to be around 480-510 nm 46,47 but they are blue shifted if the size is in a nano-domain 48 due to the quantum confinement effect.…”
Section: Emission Spectroscopy Of Camoo 4 and Srmoomentioning
confidence: 99%
“…Please refer to the web version of this article for interpretation of the color references.Highest emission of HA was detected at  EM = 310 nm (4.00 eV) after being exited with h EX > 5 eV, figure 5a. The band gap energies increase straight with the structural order46 , so the requirement of excitation energy of about 1.5 eV inferior to the E g implies that behind this effect we should have a transition involving at least one bound state located in the gap, most probably associated with defects. In the previous section, we havedemonstrated that both HA and HA/MoO x specimens presented distortions in their lattice and in their interatomic composition.…”
mentioning
confidence: 99%
“…In particular, for nano-HA/MoO x (II), experimental data agree with reported literature values observed for the OH vacancy hydroxyapatite cell ( E g ≈ 5.5 eV), so we assume that its structure mostly accords with the latter. The nano-HA/MoO x (III) specimen, conversely, presented an E g of 4.77 ± 0.11 eV, associated with the presence of the powellite phase ( E g ≈ 4.70 eV), displaying multi-phonon and multilevel processes within the band gap interfering with the OH vacancies, V OH . The extent of V OH electronic states was computed from photoluminescence data and provided in Figures S3–S5 in the SI; a clear increase in the peak intensity can be seen for nano-HA/MoO x (II) at the characteristic emission wavelength of V OH (λ EM = 460 nm), which implies an increase in these electron acceptor states.…”
Section: Resultsmentioning
confidence: 98%